FAKTOR-FAKTOR YANG MEMPENGARUHI NYERI KEPALA PASKA ENDOVASKULAR COILING PADA PERDARAHAN SUBARAKHNOID - Puspita Ratnasari, Nurlia; Desti Ramadhoni, Pinto; Sugiharto, Henry; Octavinawaty, Lenny; Haswatty, Bayu (PERDOSNI, 2024)
Introduction: Post endovascular coiling headache, according to ICHD-3, defined as a new headache due to coiling embolization which is still felt by aneurysm rupture subarachnoid patients 3 months after the procedure, which other acute SAH-related headaches have been ruled out. A previous prospective study showed that 50% unruptured aneurysms patients who undergo endovascular coiling experience headache. However, there are currently no studies on headache after endovascular coiling in ruptured aneurysms. Aim: To identify the factors that influence post-endovascular coiling headache in subarachnoid hemorrhage patients with aneurysm rupture. Method: Retrospective cohort study, using medical record data at RSUP Dr. Mohammad Hoesin Palembang. Headache intensity was assessed using the Numerical Pain Rating Scale at 3 months after the procedure according to the ICHD-3 standard. Results: Most patients were > 50 years old, female (60.5%), had a history of hypertension (81.40%), Hunt and Hess grade 2 (41.9%), mFisher grade I (41.9%), located in ICA ( 34.9%), aneurysm diameter 5 mm (69.8%), onset of action at 10 days (58.1%), mRRC class I (53.5%) and Packing Attenuation 25% (53.5%). It was found that 50% of the subjects experienced mild headache after endovascular coiling. In bivariate analysis, it was found that Hunt and Hess 4-5 (p=0.048) and Packing Attenuation >25% (p=0.03) had a significant relationship with incidence of post-endovascular coiling headache. Discussion: Severe Hunt and Hess grade (4-5) and high packing attenuation (> 25%) are associated with the incidence of post-endovascular coiling headache in aneurysm rupture SAH patients Keywords: Subarachnoid haemorrhage, aneurysm rupture, Endovascular coiling, Headache